Estrategia didáctica “Produtex” basada en los modelos de composición escrita para acrecentar la producción de textos descriptivos en el área de comunicación en los estudiantes de 3er grado de primaria de la I.E José Carlos Mariátegui - Agip Pérez, Madali (2011)
Writing's dominion is enough itself writing and once what writes to each other was reflected on;because,he permits this expressing by means of the in k and the paper yo u dream them up of the thought. In this sense,show it(subj) investigation intended to for the sake of experiencing the effects the didactic strategy PRODUTEX once was based in the composition models written to increase the production leve! of descriptive texts in the communication area in the primary school students third-degree of the lnstitution Educative Experimental " the sector's José Carlos MariáteguiRupacucha, Rioja's district. Once lnvestigation Was said it carne under a system taking as person giving a reference theoretic contributions,background of existent investigations and the composition models referidos for CASSANY: 1 model of the stages, 1 model of the word-processors, 1 model of the academic abilities and the cognitive model. Based in the mentioned models,the fact-finding hypothesis in the terms was formulated following:lf he becomes elaborate and experience didactic strategy PRODUTEX once was based in the composition models written, then will increase the production level of descriptive texts in Communication's area in the primary school students third-degree of the sector's lnstitution Educative. Experimental José Carlos Mariátegui Rupacucha, Rioja's district. The sign once was selected in order to the study was shaped for the lnstitution Educativa Experimental José Carlos Mariátegui FEH'S fourteen students of the primary school third degree - R - sector Rupacucha, Rioja's district. To the mentioned sign administrated him a pre test to evaluate the production level of descriptive texts that were possessing befare the didactic strategy's application PRODUTEX,straightaway the strategy's eight sessions proposed developed themselves. Once this period was culminated,it was administrated the behind test to determine the manufactured effects for the strategy. Once obtenidos the data of the pre and after test, he ca me from to the analysis and respective interpretation the same things,getting confirmed PRODUTEX has increased significantly than the didactic strategy's application the production level of descriptive texts in the communication area in the primary school students thirddegree of 9,21's average obtained in the pre test to 13,93's average in need in the behind test just as it is demonstrated with the hypothesis test.